Cognitive Load and Learning in the Study of Multiple Documents - Cerdan, Raquel; Candel, Carmen; Leppink, Jimmie (Frontiers in Education, 2018)
This study had two main purposes. First, to test how the availability of documents in multiple document reading might affect students’ levels of cognitive load. Secondly, to develop an instrument that captures the different sources of load when working with multiple documents. A total of 125 secondary school students read four short texts on transgenic foods and subsequently responded to an open-ended question that required them to write an essay expressing their personal stance towards the topic. Participants in the experimental treatment condition (n = 54) were allowed to go back to the texts any time during the essay task, whereas their peers in the control condition (n = 71) were not allowed to do so. As hypothesized through the lens of cognitive load theory, the cognitive load arising from cognitive processes that in themselves do not contribute to learning (i.e., extraneous cognitive load) was somewhat lower in the experimental treatment condition, probably due to split attention effects in the control condition. However, no statistically significant differences were found in perceived task complexity or learning task performance. A reliable instrument to measure different sources of intrinsic and extraneous load in multiple document reading is provided. Implications of these findings for future research are discussed.